The etiological pattern of diseases in pregnant women with enhanced blood AlAT and AsAT activities, admitted to the obstetric unit of an infectious diseases hospital - Kristina Rubenovna Dudina; Ol'ga Olegovna Znoyko; Yuliya Georgievna Trubitsyna; Svetlana Anatol'evna Shut'ko; Vladimir Nikolaevich Kuz'min; Avet Grigor'evich Serobyan; Naira Rubenovna Revazyan; Natal'ya Petrovna Petrova; Natal'ya Petrovna Blokhina; Nikolay Dmitrievich Yushchuk; K R Dudina; O O Znoiko; et al. (Терапевтический архив, 2010)
Aim: to define a role of hepatotropic (HAV, HBV, HCV, and HDV) and opportunistic hepatotropic (HGV, CMV, EBV, HHV types 1, 2, and 6) viruses in the etiological pattern of diseases accompanied by enhanced blood AlAT and AsAT activities in pregnant women. Subjects and methods. Two hundred and eleven pregnant women, including 123 patients with chronic viral hepatitis, 74 with enhanced blood AlAT activity and no markers of viral hepatitis (EAlAT-NMVH), and 14 with acute viral hepatitis were examined. Results. Most pregnant women with chronic HBV and HCV infections were found to have HBV DNA and HCV RNA in the blood in the presence of normal and enhanced activities of transaminases. In the EAlAT-NMVH group, there was none of the opportunistic hepatotropic viruses in more than 7% of cases. No genetic material of HAV, HBV, HCV, HDV, HGV, CMV, EBV, HHV types 1, 2, and 6 was found in the blood of all 10 patients with hepatitis of unspecified etiology. Conclusion. In the absence of serologic data supporting the presence of infectious pathology, blood testing using the polymerase chain reaction is of low informative value in detecting opportunistic hepatotropic viruses in pregnant women with hepatitis of unspecified etiology. However, by keeping in mind that the spectrum of opportunistic hepatotropic viruses is not confined to those included in this study, it is expedient to examine additionally pregnant women with enhanced blood AlAT and AsAT activity in order to identify TTV, B19V, HHV-8, SEN and NV-F in the blood.